(3LQjOI GdCQH hNQjOI cd SGQH TGQHs - (3GdHcQj, eUWai Hf ceGd GdOjf Hf Ydj, J(B1162(3g`s ((3YHO GdQMef Hf GHG jRjO GdHdjS GdTGaYjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj aJM HGdUdGI hGdJSdje dCgd GdJYdje HGHg hHYO ajbhdeUWai GdUOjbjGSJNQJ Gddg JYGdi aj hVY UdhGJ fHhjIhSejJgG LQjOI GdeBQH hNQjOI cd SGQH TGQHs
(3BNQgG (B:s
(3eG GfHSW HSGW GdOjf HgOjI GdeJjf GdeHjf HSWG heG CRGd Gddg Hg bHVG haJM Hg HSWGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 239s
(3eYLe GdeDdajf(B: 3 / 876s
(3EjVGM Gdecfhf(B: 1 / 361s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs